Multifunctional Pyridinium Systems for Nonaqueous Redox Flow Batteries. (25th October 2017) - Petty, Anthony; Mann, Shane C.; Dumitrascu, Adina; Olson, Kevin; Guarr, Thomas F.
Abstract : Systems which rely on the electrochemical or chemical reduction of pyridinium compounds and their 4, 4'-bipyridinium (viologen) counterparts are ubiquitous, owing in large part to the inherent stability of the resultant radical species. By contrast, however, the corresponding phenylene-bridged bis(pyridinium) compounds have received far less attention. Nevertheless, such materials can be readily prepared from inexpensive starting materials and display potentially useful electrochemical behavior. In this paper, we detail the reversible multielectron reduction (2e - and in some cases, 4e - ) of numerous phenylene-bridged bis(pyridinium) species and describe their potential use in nonaqueous redox flow battery (RFB) applications. In addition, several systems in which pyridinium or bis(pyridinium) anolytes are covalently linked to potential RFB catholytes such as ferrocene, carbazole, orphenothiazines have been prepared and electrochemically characterized.